Scientific and Methodological Fundamentals of formation of basic elements in Wrestlers (Uzbek Kurash) - Zulxumor Urinbaevna Umarova; Abdusamat Abdumalikovich Umarov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
There are two traditions ‒ indigenous and international ‒ that exist side by side and are followed with equal passion by their fans. The most famous local sport is kurash, a form of wrestling which has a history that stretches back over millennia. This article analyzes the existence of some factors that affect the process of organizing the training of young wrestlers in technical movements, their negative impact on the effectiveness of competition activities and the problem of forming effective technical movements in wrestling. The article offers suggestions and recommendations on improving the scientific and methodological basis for the formation of basic elements in young wrestlers, as well as the results of the analysis of scientific and methodological literature